Apophyllite - C. M. B. Line, ILL, Grenoble, France (My University, 2000)
Inelastic Neutron Scattering spectrum of Apophyllite, KCa4Si8O20(F,OH).8H2O, measured on the TFXA instrument. Exact formula Na0.1Al0.07K0.92Ca4.1Si8.1O20 (F not determined).
Keywords: TFXA